Relationship between Emotional Intelligence and Academic Stress of Students - Rani, Usha (Innovative Research Thoughts, 2017)
In today's high-stress atmosphere, students at all educational levels need to have high levels of emotional intelligence in order to succeed academically. Emotional intelligence refers to the ability to recognise and comprehend one's own and others' feelings. Emotional intelligence may be developed. In other words, it's the capacity to recognise and express one's emotions. As a person's personality is defined by their emotions, it is possible to discern the underlying social patterns. Developing students' emotional intelligence is critical to the educational process because it gives them the tools they need to deal with difficult situations. Self-awareness, empathy, self control, self-management and collaboration are all aspects of emotional intelligence. Those who have a high level of emotional intelligence are more creative and more successful.